Jacob the Baker - BenShea, Noah (Villard Books New York, 1989)
Jacob the Baker is the International Best Selling and timeless story about a man whose humble life and profound wisdom are a source of both inspiration and reflection to those around him. Eighteen years in the writing, this deceptively simple book kindles the human spirit in the manner of a modern classic, its gentle message inviting each of us to witness that "a miracle is often the willingness to see the common in an uncommon way."Jacob is a poor but pious figure who rises anonymously before dawn to light the ovens in the town bakery. As the ovens are warming and the first dough rising Jacob turns inward, scribbling notes to himself -- thoughts and observations ringing with the clarity of a soul unencumbered by "the weight of its own importance."One of Jacob's carefully folded notes is accidentally baked into a loaf of bread. When it is discovered and read, its impact is overwhelming. The secret of Jacob soon becomes a whisper that rides the wind into every ear, and the community embraces Jacob "as if he were a long-ignored human treasure suddenly unearthed."Adults and children alike gather at the bakery or stop Jacob on the street. With patience and love, Jacob the baker finds doors for those locked within themselves and their presumptions, and turns the key to their questions.Jacob the Baker is a treasury of answers in the form of brief stories and parables, told by a baker who is a poet of truth and kindness. The questions put to Jacob are as diverse as death and charity, eternity and anger, but Jacob's responses are always a celebration of rightness, a reminder of the purpose and order in life. He is a wise and gentle friend who renews our sense of belonging to the world.Jacob the Baker can be started on any page; as Jacob would say, it doesn't matter where you start, it matters that you start.
Gentle Wisdom for a complicated world
Keywords: Conduct of life